MODEL OF A MUNICIPAL SYSTEM OF SPORT And LEISURE FOR The MANAUS-AMAZONAS CITY (Fiep Bulletin - online, 2014)
The present study of exploratory and descriptive nature has as objective to present for quarrel a model of Municipal System of Sport and Leisure for the city of Manaus-Amazonas, as from the proposal approved in the I National Conference of the Esporte/2006. For data collection it was used Documentary Research, from the set of proposals proceeding from the States. The results of the State Conferences are presented, as well as of the Resolution of the II National Conference of Sports, approved in the final plenary of the respective Conference.
Keywords: Sportive Management; System Sportive; Sport